THE ROLE OF TECHNOLOGY IN TEACHING LISTENING - Aryuliva Adnan (International Conference on Languages and Arts, 2016)
It cannot be denied that the development of technology has made the great impact to teaching listening. Every language teacher has realized that teaching listening needs materials and media that cannot be separated from technology. Teaching listening needs audio materials of native speakers for learning activities insides the classroom or for students' practices outside the classroom. Over the years English teachers have used tape recorder and cassetes in teaching listening, even though these media can be categorized as the simple media and technology. ....